+0  
 
0
34
1
avatar

https://web2.0calc.com/questions/help_35018

 May 14, 2020
 #1
avatar+20906 
0

f(x)  =  (1 + x) / (1 - x)                     g(x)  =  -2 / (x + 1)

 

f(12)  =  (1 + 12) / (1 - 12)  =  13 / -11                   g( f(12) )  =  -2 / ( 13/-11 + 1 )  =  11

 

Next iteration: 

 

f  =  ( 1 + 11) / (1 - 11)  =  12 / -10                         g  =  -2 / ( 12/-10 + 1)  =  10

 

Next:

 

f  =  ( 1 + 10) / (1 - 10)  =  11 / -9                            g  =  -2 / ( 11/-9 + 1)  =  9

 

Keep going ...

 May 14, 2020

11 Online Users

avatar